Determinants of the operation of Poland’s water utilities - Chudziński, Paweł (Management Sciences, 2018)
The aim of this paper is to present the situation of Polish water utilities from the perspective of cost benchmarking against the background of international experience, and to discuss the merits of using benchmarking with a view to improving water utilities efficiency. The text examines the income side of the issue by focusing on the water tariff levels used by Polish water utilities. The author’s experience is that the first effects of using benchmarking in cost management are achieved after about three years of participating in benchmarking project. Another important threat is the difficulty in finding benchmarking partners or a proper benchmarking project. The third one, in the author’s view the most significant, is an inadequate preparation of benchmarking indicators. The implementation of benchmarking of cost management at Aquanet SA produced measurable results, presented in this paper. It could be concluded, therefore, that using this method of cost management contributes to cost efficiency and, as a result, increases the efficiency of water utilities
Management Sciences, 2018, vol. 23, no. 1, s. 13-19
Keywords: benchmarking; water utility; efficiency; water tariffs; przedsiębiorstwo wodociągowe; efektywność; taryfy za dostarczanie wody